AL-‘ALAJA AL-NAFSII FII ANA MUTASIF LI SAMIH AL-QASIM - Rahmi Rahmiati; Zulkhairi Sofyan (An-Nahdah Al-'Arabiyah is published by Department of Arabic Language and Literature in cooperation with The Center for Research and Community Service (LP2M), 2022)
Abstract : This articel aims to examine the Psychotherapy Aspect of a servant in his prayer on Qasidah Samih Al- Qaseem “’Ana muta’assif